Phylum Tardigrada: A re-evaluation of the Parachela - Marley, Nigel J.; Mcinnes, Sandra J.; Sands, Chester J. (Zootaxa, 2011)
We assessed the available morphological evidence to see if this corroborates the paraphyly in the Parachela (Tardigrada) as suggested by recent molecular data. We reconcile molecular phylogenetics with alpha morphology, focusing on claw and apophysis for the insertion of the stylet muscles (AISM). We combine molecular and morphological evidence to define six new taxa within the Parachela Schuster et al 1980. These include two new families of Isohypsibiidae fam. nov. and Ramazzottidae fam. nov. along with four new superfamilies of Eohypsibioidea superfam. nov., Hypsibioidea super- fam. nov., Isohypsibioidea superfam. nov., and Macrobiotoidea superfam. nov.